2007
DOI: 10.1590/s1517-83822007000300025
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas spp. and microbial indicators in raw drinking water source

Abstract: Aeromonas species are autochtonous in the aquatic environment and some of them have been associated with health effects like wound infections, septicemia and diarrhoeal illness. In this study, the occurrence of Aeromonas spp. and microbial indicators in raw drinking water from wells, springs, fountains and mineral waters was evaluated. A total of 126 water samples was analyzed for Aeromonas spp. by the membrane filtration technique using ADA media and by P/A test. Typical colonies of Aeromonas spp. were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
2
6
0
3
Order By: Relevance
“…In this respect, a study was conducted on Mfoundi River watershed at Yaounde in Cameroon, in which the recorded values of Aeromonas were about twofold higher than fecal coliforms . Our results were also in harmony with those previously reported by Kivanc et al Dumonter et al , and Di Bari et al .…”
Section: Resultssupporting
confidence: 92%
“…In this respect, a study was conducted on Mfoundi River watershed at Yaounde in Cameroon, in which the recorded values of Aeromonas were about twofold higher than fecal coliforms . Our results were also in harmony with those previously reported by Kivanc et al Dumonter et al , and Di Bari et al .…”
Section: Resultssupporting
confidence: 92%
“…2007). Exposure to water contaminated with Aeromonas spp., through ingestion or contact, has been associated with human infections, which are particularly hazardous in immune‐compromised patients (Bari et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are data that illustrate the spread of autochthonous micro‐organisms in an aquatic environment, with a high prevalence of some species of Aeromonas and Vibrio , occurring mainly in fresh water fish (Hirsch et al. 2006; Bari et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A regular incidence of C. perfringens spores in groundwater samples from public springs used for direct human consumption was detected in Spain (Araujo et al, 2004) where 40 of 51 groundwater samples analyzed (78.4%) were found to be positive for C. perfringens spores. Di Bari et al (2007) in São Paulo, Brazil, reported the presence of C. perfringens in 16.5% (103 samples) of the drinkable water sources analyzed. Bonde (1963) suggested that all SRCS in waters are not indicators of fecal pollution and that C. perfringens is the appropriate indicator.…”
Section: Discussionmentioning
confidence: 99%